Antennal ultrastructure of three species of Cyclocephala Dejean, 1821 (Coleoptera: Scarabaeidae) - Rodrigues, Sérgio Roberto (2024)
This study describes the antennal ultrastructure in Cyclocephala forsteri Endrodi, 1963, Cyclocephala melanocephala (Fabricius, 1775) and Cyclocephala tucumana Brethes, 1904 (Coleoptera: Scarabaeidae). Adult of Cyclocephala Dejean, 1821 specimens were collected using a light trap placed near a pasture area, segregated by gender, based on male-specific dilated pre-tarsomeres and preserved in 70% alcohol. Scanning electron microscopy (SEM) images of the antenna lamellae were obtained from ten specimens at Universidade Estadual Paulista (UNESP) in Ilha Solteira, SP, Brazil. We identified trichoid, chaetic, placoid, coeloconic, basiconic sensilla, and pores in antenna of all the species. Placoid sensilla were prevalent in the antennal lamellae. The antennae of C. forsteri females had 5,457 sensilla, of which 5,327 (97.62%) were placoid, 123 (2.25%) coeloconic, and seven (0.13%) basiconic, while the antennae of males showed 5,351 sensilla, with 5,238 (97.89%) being placoid, 100 (1.87%) coeloconic, and 13 (0.24%) basiconic. The antennae of C. melanocephala females presented 6,814 sensilla, with 6,581 (96.58%) being placoid, 231 (3.39%) coeloconic, and two (0.03%) basiconic; while those of males had 6,333 sensilla, with 6,023 (95.11%) being placoid and 310 (4.89%) coeloconic. Finally, the antennae of C. tucumana females had 1,981 sensilla, with 1,845 (93.13%) being placoid, 127 (6.42%) coeloconic, and nine (0.45%) basiconic; while the antennae of males had 3,756 sensilla, with 3,656 (97.34%) being placoid, 99 (2.64%) coeloconic, and one (0.02%) basiconic. Overall, adults of C. melanocephala and C. tucumana presented dimorphism in the antennal sensilla.